Associations of different inflammatory factors with atherosclerosis among patients with psoriasis vulgaris - Huong, Nguyen Thi Kim; Long, Bui; Doanh, Le Huu; Thoai, Tran Minh; Hang, Nguyen Thi; Khoi, Le; Nu, Pham Thi (Frontiers in Medicine, 2024)
Background This study aimed to measure the associations between different inflammatory factors, namely interleukin (IL)-17A, tumor necrosis factor (TNF)-α, and high-sensitivity C-reactive protein (hs-CRP), and atherosclerosis in patients with psoriasis vulgaris. Methods A cross-sectional study was conducted at two hospitals in Hanoi, Vietnam. A total of 125 patients with psoriasis vulgaris and 50 healthy controls were recruited. Clinical characteristics and atherosclerosis were assessed. IL-17A, TNF-α, and hs-CRP levels were measured. Results Psoriasis vulgaris patients with atherosclerosis had higher levels of hs-CRP (median = 1.22; interquartile range—IQR = 0.34–12.11) and IL-17A (median = 1.30; IQR = 0.43–4.28), but a lower level of TNF-α (median = 0.54; IQR = 0.13–3.41) compared to those without atherosclerosis (p < 0.05). Only LogIL-17A was positively related to atherosclerosis in psoriasis patients (Odds Ratio—OR = 2.16, 95% CI = 1.06–4.38, p < 0.05). After excluding systemically treated patients, LogIL-17A and Log TNF-α were associated with the likelihood of atherosclerosis (p < 0.05). Conclusion This study suggests a link between elevated levels of IL-17A and TNF-α and subclinical atherosclerosis. Further investigation on a larger scale is required to establish the causality of this relationship.